Streptococcus Mutans and Enterococcus Gallinarum Isolated from Dental Abutments for Patients with Periodontitis - Hussein, Alaa Ali; Karomi, Asma Sumiea; Mosses, Wisam R. (International Journal of Medical Toxicology and Legal Medicine, 2024)
Background: Periodontitis impacts a sizable proportion of the population. As the condition progresses, periodontal abscesses, tooth loss, and pain are all serious problems. It has also been shown that periodontitis is connected to health concerns outside of the mouth. Material and methods: This study included 230 samples ranging in age from 40 to 71 years (200 patients and 30 controls). From July 2022 to October 2022, patients in Kirkuk were referred to three key facilities: the dental specialist center, maxillofacial surgical center, and department of periodontics in Azadi Teaching Hospital, and the specialist consulting clinic. The genomic DNA was obtained using the Wizar genomic DNA purification kit (Promega, Madison, WI, USA), which is intended to recover bacterial DNA from both species with various gram counts. On 5 samples of DNA isolated from Enterococcus gallinarum, PCR was done using primers. Five DNA samples from various strains of Streptococcus mutans were subjected to polymerase chain reaction amplification of the van C-1 and ermB genes. Results: The outcomes of genetic testing Vancomycin resistance gene vanC-1 for Enterococcus gallinarum (80%) and Erythromycin resistance gene ermB for Streptococcus mutans (100%). The convergence of the nitrogen base of the two bacteria with the NCBI was observed through the analysis of the Phylogenetic tree for four genes, where they were identical to the proportion of (96.92%) for van C-1 gene for Enterococcus gallinarum and (100%) for ermB gene for Streptococcus mutans. Conclusions Vancomycin resistance gene vanC-1 for Enterococcus gallinarum and Erythromycin resistance gene ermB for Streptococcus mutans (both genes were found in NCBI)